國中生內、外在學業希望信念之建構及其相關因素之探討 Internal and External Loci of Academic Hope Belief for Junior High School Students and Their Relationship With Related Factors - 張映芬 Ying-Fen Chang (National Taiwan Normal University, 2019)
過去研究甚少探討希望信念來源，且很少將此議題分析於國中生的學業希望信念。因此，本研究建構三個驗證性因素分析競爭模式以探討國中生學業希望信念分類架構，以及建構「希望信念與其相關因素之歷程模式」以分析自我觀、希望信念、情緒、行為之關係。本研究抽 取兩批國中二年級學生為樣本，共 1,079 人，以結構方程模式進行分析。研究結果顯示：一、「希望信念來源二階模式」比「路徑／動力思考二階模式」、「四向度希望信念模式」更適配；二、「希望信念與其相關因素之歷程模式」與觀察資料適配；三、獨立我、相依我分別正向預測內、外在希望信念；四、內、外在希望信念分別正向預測自豪、感恩；五、自豪、感恩分別正向預測求助行為、助人行為；六、外在希望信念正向預測求助行為。 Few studies have explored the locus of hope belief with respect to junior high school students' academic hope belief. Therefore, the purpose of this study was to construct three competing confirmatory factor analysis models of hope belief and a model of hope belief and its related factors to test how the models fit with the observed data and to analyze the relationships between self-construal, hope belief, emotions, and behavior. The participants were 1,079 junior high school students, and structural equation modeling was used. The following results were obtained: (1) The second-order model of the locus of hope belief fit the observed data better than the other two competing models. (2) The model of hope belief and its related factors fit the observed data well. (3) Independent and interdependent self-construal positively predicted internal and external loci of hope belief, respectively. (4) Internal and external loci of hope belief positively predicted pride and gratitude, respectively. (5) Pride and gratitude positively predicted help-seeking and helping behavior, respectively. (6) An external locus of hope belief positively predicted help-seeking.